MULTIZEN A multisensory installation designed for individuals with profound intellectual and multiple disabilities - PEÑA CASTRO, ANGELA; VANKY, MARTIN (My University, 2020)
Multisensory environments are today being used as a form of alternative therapy available for people with profound intellectual and multiple disabilities where the focus lies on creating a relaxing and positive experience for these individuals. However, many installation within these environments can consists of switch-like interactions which can offer the user less exploration and playfulness compared to more dynamic installations. The aim of this thesis is to shed some light on which aspects to consider when designing multisensory installations for people with profound intellectual and multiple disabilities. The thesis was conducted in collaboration with Eldorado, where members of the staff participated due to the target group not being available as a result of COVID-19. The results showed that important aspects to consider include: stimulating more than one sense, customizing for different capabilities, having a clear mapping between input and output, balancing the level of complexity in the interaction as well as having an installation that both looks and feel appealing to the user.
Keywords: multisensory environments; installation; profound intellectual and multiple disabilities; music therapy